The geographical expansion of Daish organazitaion in Iraq and its impact on sustainable food security (plant production as an example) - Al-Boutani , Talaat Mohamed Taher Omar (Zanco Journal of Human Sciences, 2021)
Since the fall of the Iraqi regime in 2003 and the entry of American forces, the security situation in Iraq has worsened as a result of rgence of armed movements that were fighting Iraqi security forces and American forces together. After ISIS invasion, the security situation was seriously worsened, and ISIS controlled large parts of the governorates of Nineveh, Anbar, Salah al-Din, Kirkuk, Diyala. Iraqi bread basket for winter crops that secure (50%) of strategic crops in Iraq and summer crops go hit very hard. The ISIS group intentionally targeted the main food producing areas, and as a result the agricultural sector sustained significant economic losses; including destruction and burning large areas of land, agricultural facilities, and irrigation projects. Lack of agricultural production, looting of grain stores and agricultural crops, led to a reduction in the cultivated areas in the region and a decrease in agricultural production and lack of sustainable food security in the study area and Iraq, and thus a deficit Local production in food security, and the food gap is bridged by import. The result is the total damage and losses to the agricultural sector in the study area (1.819) billion USD for one year